FUZZY LOGIC DALAM PENENTUAN PRESTASI SISWA SESUAI STANDAR KOMPETENSI SEKOLAH - Denny Hasminta Sembiring (UPPM, 2017)
Interest standard represent the reference in measuring achievement especially achievement of student grad. However, reference in predict of student achievement sometimes less be clear. Hence is in this case used by logic fuzzy for the purpose of here is that possible existing value can be packed into more than one gathering category with the different membership value from each gathering. Input parameter used here own 3 especial standard component that is Attitude,Knowledge, and Skill.